Two new genera and four new species of fossilweevils (Coleoptera: Curculionoidea) in Baltic amber - Legalov, Andrei (Entomologica Fennica, 2016)
Two new genera, Palaeodexipeus gen. n. (type species: Palaeodexipeus kirejtshuki sp. n.) and Succinalophus gen. n. (type species: S. attenboroughi sp. n.), and four new species, Oxycraspedus poinari sp. n., Palaeodexipeus kirejtshuki sp. n., Dorytomus electrinus sp. n. and Succinalophus attenboroughi sp. n., are described and illustrated. These are the first records of the tribes Oxycraspedini in the family Belidae, and Stromboscerini and Tropiphorini in Curculionidae in the Baltic amber.